Ecosystem services for intensification of agriculture, with emphasis on increased nitrogen ecological use efficiency. Issue 2 (7th February 2020) - Sena, Virley G. L.; de Moura, Emanoel G.; Macedo, Vinícius R. A.; Aguiar, Alana C. F.; Price, Adam H.; Mooney, Sacha J.; Calonego, Juliano C.
Abstract: In weathered tropical soil, low nutrient use efficiency can lead to agricultural systems becoming unsustainable. Therefore, tropical agriculture is highly dependent on ecosystem services, such as nutrient recycling and carbon sequestration, to enhance soil fertility, increase nutrient uptake, and facilitate sustainable production of agricultural goods. This research aimed to find the balance between sustainability and profitability of tropical agriculture by evaluating the changes in soil caused by the ecosystem services provided by the biomass of leguminous trees ( Gliricidia ) and assessing how these changes (associated with potassium) can affect nitrogen‐use efficiency and maize yield. An experiment was conducted testing the impact of Glircidia biomass addition vs. bare soil, with or without addition of both nitrogen and/or potassium. Changes in soil organic matter, (SOM) base cations sum, soil resistance, N uptake, N‐use efficiency, and maize yield were evaluated. Gliricidia biomass, when used with N and K, contributed to increasing SOM by 5.0 g/kg and the sum of base cations by 1458. 65 kg/ha in the 0–30 cm layer. Moreover, grain yield was increased by approximately 70% in the treatments with Gliricidia when compared to treatments without biomass where yield was very low. In bare soil, the additional yield of 1.5 tons/ha would not be enough to convince farmers to change slash and burn to conventional bare soil systems. Our results showed that leguminous trees, such as Gliricidia, might contribute to ensuring sustainable agricultural intensification in humid tropical soils with low natural fertility by providing ecosystem services such as biomass production, carbon sequestration, base cation recycling, and increased N acquisition. These findings might be an important strategy to replace the common slash‐and‐burn‐system and preserve the rainforest against the traditional shifting cultivation system. In contrast, the conventional system with bare soil showed that the addition of nitrogen was unfeasible, mainly in conditions of high rainfall precipitation. In these circumstances, the use of potassium may increase nitrogen‐use efficiency only when biomass is not used.